2001
DOI: 10.1126/science.1062939
|View full text |Cite
|
Sign up to set email alerts
|

The Centromere Paradox: Stable Inheritance with Rapidly Evolving DNA

Abstract: Every eukaryotic chromosome has a centromere, the locus responsible for poleward movement at mitosis and meiosis. Although conventional loci are specified by their DNA sequences, current evidence favors a chromatin-based inheritance mechanism for centromeres. The chromosome segregation machinery is highly conserved across all eukaryotes, but the DNA and protein components specific to centromeric chromatin are evolving rapidly. Incompatibilities between rapidly evolving centromeric components may be responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
1,156
5
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,173 publications
(1,210 citation statements)
references
References 83 publications
43
1,156
5
6
Order By: Relevance
“…The centromere of chromosome 2 was previously assigned to positions which correspond to the chromosomal regions of either the 45S rDNA, the major or the minor Type III repeat signals [8,25,28]. CENH3 is a good marker for assaying centromere activity since it is found only in functional centromeres in eukaryotes [29-35]. The preparation of anti-CENH3 antibody in cucumber would be used to prove the location of functional centromere on cucumber chromosome 2.…”
Section: Discussionmentioning
confidence: 99%
“…The centromere of chromosome 2 was previously assigned to positions which correspond to the chromosomal regions of either the 45S rDNA, the major or the minor Type III repeat signals [8,25,28]. CENH3 is a good marker for assaying centromere activity since it is found only in functional centromeres in eukaryotes [29-35]. The preparation of anti-CENH3 antibody in cucumber would be used to prove the location of functional centromere on cucumber chromosome 2.…”
Section: Discussionmentioning
confidence: 99%
“…The centromeres of most eukaryotic chromosomes have particular genetic and chromatin configurations. Typically, centromeres are composed of one or more families of tandem repetitive element, and centromeric nucleosomes contain special histone variants [40].…”
Section: Formatting For Replication For Transmission To Daughter Cellsmentioning
confidence: 99%
“…Fifteen years ago, Henikoff et al (2001) proposed a model of centromere drive to explain why centromeric chromatin and fundamental kinetochore proteins -despite their highly conserved function in faithful chromosomal segregation -are rapidly evolving instead of being fixed at one optimal state. They suggested that kinetochore proteins are in evolutionary conflict with centromeric satellite DNA that exploits asymmetric female meiosis to secure its preferential transmission to the egg (which is the only surviving meiotic product) at the expense of its homologous counterpart.…”
Section: Introductionmentioning
confidence: 99%